1956
DOI: 10.1021/ac60110a026
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Cadmium and Zinc

Abstract: Zinc and cadmium form negatively charged chloride complexes which are adsorbed by the strongly basic anion exchange resin Dowex 1. Maximum adsorption of zinc and cadmium is obtained in 0.12V hydrochloric acid containing 100 grams of sodium chloride per liter.In this medium most elements with which zinc and cadmium are associated in metals and minerals are not

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1964
1964
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…We adopted the method by Kallmann et al [ 21 ] to purify Cd from other metals. It uses the difference in stability between the negatively-charged chloro-complex of Cd and other metals in a HCl solution (Cd chloro-complex is more stable than the chloro-complexes of other metals) and separates Cd from other metals using an anion-exchange resin.…”
Section: Methodsmentioning
confidence: 99%
“…We adopted the method by Kallmann et al [ 21 ] to purify Cd from other metals. It uses the difference in stability between the negatively-charged chloro-complex of Cd and other metals in a HCl solution (Cd chloro-complex is more stable than the chloro-complexes of other metals) and separates Cd from other metals using an anion-exchange resin.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the AG MP-1M was expected to be superior to a gel type one in terms of chemical resistance and dry hardiness. Although the mixed acids of HCl and HF were often used for Cd separation with the anion exchange resin, 1,[10][11][12] according to the report by Anders et al, 13 we used only 0.3 mol dm -3 HCl in order to simplify the separation procedure of Cd. In the preliminary experiment, Cd (0.5 g, 8.8 meq) was loaded on the AG MP-1M resin column (bed volume; 26 mL, exchange capacity; 26 meq).…”
Section: Determination Of the Weight Distribution Coefficient Dwmentioning
confidence: 99%
“…Nitric acid of 1.0 mol dm Ϫ3 was used as an eluent solution according to the literature. 5) In the flow system shown in Fig. 1, the effects of flow rate and sample volume were examined.…”
Section: ϫ3mentioning
confidence: 99%
“…Kallmann et al reported the separation procedure for zinc from some elements, using a strongly basic anion exchange resin. 5) In their method, zinc(II) formed anion species in a hydrochloric acid solution and was adsorbed on the resin, while iron(III) was not adsorbed on the resin because the negatively charged iron(III) chlorides were hardly formed under the experimental conditions. In this way, the separation using the anion exchange resin will be a potential pretreatment method for the determination of zinc in a steel sample solution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation